The social impact of the influenza pandemic of 1918-19: with special reference to the East Midlands - Knight, Joan Eileen (2015)
The purpose of this study was to explore the social impact of the 1918-1919 influenza pandemic, known as 'Spanish influenza', on the lives of the people of the East Midlands (defined as Leicestershire, Nottinghamshire and Derbyshire). A range of primary and secondary literature revealing the global impact of the event was examined, together with literature focusing on Britain and the east Midlands region to enable appropriate comparisons to be made and the East Midlands' experience to be contextualised.